2006
DOI: 10.1016/j.jtcvs.2005.10.060
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative cyclooxygenase 2 inhibition to reduce tumor cell adhesion and metastatic potential of circulating tumor cells in non–small cell lung cancer

Abstract: Celecoxib significantly reduced establishment of metastases by circulating tumor cells in a murine model. It also inhibited CD44 expression and extracellular matrix adhesion in vitro. Perioperative modulation of cyclooxygenase 2 may be a novel strategy to minimize metastases from circulating tumor cells during this high-risk period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…PGE 2 enhances the metastatic process via multiple mechanisms that in combination yield a strong pro-metastatic effect. The effects of PGE 2 that promote metastasis include upregulation of the cell adhesion receptor, CD44 (56, 58, 59), induction of a transition from an epithelial to a mesenchymal phenotype (16, 20, 60), activation of matrix metalloproteinases (23, 54, 61), enhanced tumor cell migration (62), increased angiogenesis (63), and disruption of the immune surveillance of tumor cells (24, 26, 6466). …”
Section: Discussionmentioning
confidence: 99%
“…PGE 2 enhances the metastatic process via multiple mechanisms that in combination yield a strong pro-metastatic effect. The effects of PGE 2 that promote metastasis include upregulation of the cell adhesion receptor, CD44 (56, 58, 59), induction of a transition from an epithelial to a mesenchymal phenotype (16, 20, 60), activation of matrix metalloproteinases (23, 54, 61), enhanced tumor cell migration (62), increased angiogenesis (63), and disruption of the immune surveillance of tumor cells (24, 26, 6466). …”
Section: Discussionmentioning
confidence: 99%
“…One study demonstrated that celecoxib suppresses cancer progression, in addition to its analgesic and anti-inflammatory effect (20). Furthermore, it has been shown that perioperative COX-2 inhibition reduces the adhesion and metastatic potential of disseminating tumors in murine models and improves cancer recurrence-free survival rates in mice undergoing primary tumor excision (21). Celecoxib may exert its antitumor effect via COX-2-dependent and -independent pathways.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of COX-2 may be upregulated in cancer cells or during the inflammatory response. Most significantly, COX-2 inhibitors repress tumor development in the lungs of cancer-treated mice [12]. It is also worth noting that the upregulation of COX-2 expression induced by a variety of stimuli was involved in the activation of the p38 MAPK and ERK pathways in A549 [33][34][35].…”
Section: Discussionmentioning
confidence: 94%
“…Preclinical studies suggest that treatment with a selective COX-2 inhibitor may enhance the antitumor effects of chemotherapy [10,11]. Perioperative COX-2 inhibition could reduce tumor cell adhesion and the metastatic potential of circulating tumor cells in non-small cell lung cancer [12].…”
Section: Introductionmentioning
confidence: 99%